Sistem Informasi Pembayaran SPP Menggunakan Whatsapp Gateway di SMK Tamansiswa Padang - Ningsih, Irda Silvia; Mulyono, Heri; Rini, Faiza (JURTEII: Jurnal Teknologi Informasi, 2022)
Currently, paying tuition fees at SMK Tamansiswa Padang is still done manually, which is still recording payment reports in a financial book. In addition, the treasurer has other obstacles, such as busy teaching and additional duties from the principal. So it takes a long time to record payments and calculate the number of payments from paying students. This information system uses the System Development Life Cycle (SDLC) method with an iterative development model. This model has several stages: design, analysis, implementation, testing, and evaluation. The research results on the spp payment information system using the WhatsApp gateway at SMK Tamansiswa Padang are from the tests carried out from black-box testing, white box testing, and beta testing to get valid results and the system can run well.